Knowledge and Attitude towards Emergency Contraceptives among Nursing and Midwifery Students in Tertiary Care Hospitals, Karachi - Fouzia Perveen; Mahjabeen Khan (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To  assess the knowledge and attitude about the emergency contraceptives among nursing and midwifery students in tertiary care hospitals in Karachi. Methods: This cross-sectional study was carried out in the nursing school of Dow University Hospital and & Civil Hospital Karachi. Duration of the study was January 2017 to June 2017. All nursing and midwifery students, after verbal consent, were interviewed face-to-face using a pretested structured questionnaire. The  questionnaire  was  developed  to  assess  knowledge  and  attitudes;  the  way  in  which the respondents think and behave  towards  emergency  contraceptives  (EC).  Some  questions  were objective in nature with 'Yes' or 'No' options, whereas few questions were of multiple choice. The variables were age, educational level, religion, marital status, source of  information,  EC  types  and  method of use, side effects and source of availability and the attitudes of participants towards the use of EC (11 items). The data was recorded in MS  Excel  (2010  version).  Data  analysis  was  done  by  SPSS 16. Mean and SD of age was calculated while the categorical variables were analysed by using frequency and percentages. Chi-square test was applied and significance of test was decided at p- value £0.05. Results: There were 149 respondents out of the 165 targeted population.  The  response  rate  was  90.30% among nurses and midwives working in public sector of health care system in Karachi, Pakistan. The mean age of  the  respondents  was  20.63  ±  1.69  years.  Most  respondents  were  between  the ages of 20-35 years; 98 (65.8%),  with  majority  having  educational  level  of  matriculation;  66  (44.3%). There were nurses and midwives with optimum knowledge  for  EC  based  on  the  scale  of  having three or more correct responses out of four items. The  best  positive  attitude  was  scaled  by correct response of seven or more items out of eleven. The association of demographic factors with attitude towards EC was only significant at p-value£ 0.05 among married students. Conclusion:  Awareness  regarding  EC  with  optimgum  knowledge  and  positive  attitude  was  found  in about two-thirds of nurses and midwives. Information must be spread through media and training to remove barriers and misconceptions among nurses and midwives.